A review of Children's Advocacy Centers' (CACs) response to cases of child maltreatment in the United States. (November 2015) - Elmquist, JoAnna; Shorey, Ryan C.; Febres, Jeniimarie; Zapor, Heather; Klostermann, Keith; Schratter, Ariane; Stuart, Gregory L.
Abstract: Child maltreatment is a serious and prevalent problem in the United States. Children's Advocacy Centers (CACs) were established in 1985 to better respond to cases of child maltreatment and address problems associated with an uncoordinated community-wide response to child maltreatment. CACs are community-based, multidisciplinary organizations that seek to improve the response and prosecution of child maltreatment in the United States. The primary purpose of this manuscript is to present a review of the literature on CACs, including the CAC model (e.g., practices, services, and programs) and CACs' response to cases of child maltreatment. This review suggests that there is preliminary evidence supporting the efficacy of CACs in reducing the stress and trauma imposed on child victims during the criminal justice investigation process into the maltreatment. However, this review also identified important CAC polices, practices, and components that need further evaluation and improvement. In addition, due to the methodological limitations and gaps in the existing literature, research is needed on CACs that employ longitudinal designs and larger samples sizes and that evaluate a larger array of center-specific outcomes. Finally, this review suggests that CACs might benefit from incorporating ongoing research into the CAC model and accreditation standards and by recognizing the importance of integrating services for child and adult victims of interpersonal violence. Highlights: This is a review of the literature on Children's Advocacy Centers (CACs). This review indicates that there's a paucity of methodologically rigorous studies evaluating the effectiveness of CACs. Past work suggests that CACs are effective in reducing the stress imposed on child victims during criminal investigations. Research also indicates that a number of CAC policies, components, and practices need further improvement and evaluation. Research using longitudinal designs and that evaluate a larger array of center-specific outcomes is needed. Limitations of the current review include potential publication bias and a lack of methodologically rigorous studies.